RAISING AWARENESS OF MYIASIS: A CASE SERIES FROM AUTOCHTHONOUS AND IMPORTED INFESTATIONS - Pavlova, Maja Jurhar; Labachevska-Gjatovska, Liljana; Kostovski, Marko; Jovchevski, Radomir; Slavevska Stamenkovic, Valentina; Hinic-Jordanovska, Jelena; Volceska, Angela; Rashikj, Ljubica; Cvetkovikj, Aleksandar (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Myiasis is an infestation of the tissues of livinghumans and other vertebrates by the immature stages (larvae) of Diptera. According to the International Classification of Diseases, myiasis belongs to the morbidity classification ICD-10-CM, with the ICD code B87 (2025 edition). Myiasis is not mandatory to report, and through our experience, we aimed to raise awareness of this infestation among medical practitioners and the public. We discuss seven cases of myiasis diagnosed over five years (2019-2024) whose specimens (larvae) was submitted to the Institute for Microbiology and Parasitology, Medical Faculty - Ss. Cyril and Methodius University in Skopje, Republic of North Macedonia. The collected maggots were analyzed through macroscopic and microscopic examination. Morphological identification of the larvae was conducted using identification keys. Photographs were taken using an Olympus SZX9 and a Carl Zeiss Stemi 508 stereo microscope with an integrated high-resolution digital camera. Our findings confirmed an infestation by larvae from two autochthonous species, Sarcophaga argyrostoma  and Lucilia sericata . We also identified an imported fly species, Cordylobia anthropophaga . The larvae can cause various symptoms depending on their relationship with the host and the anatomical location in the body. The outcome is related to comorbidities and the provision of appropriate, timely treatment. Medical practitioners should consider myiasis in their differential diagnosis. Nosocomial myiasis is a significant concern and requires special attention and preventive measures. Key words: myiasis, Sarcophaga argyrostoma, Lucilia sericata, Cordylobia anthropophaga , Republic of North Macedonia